High precision optical characterization of semiconductor saturable absorber mirrors - Maas, D. J.; Rudin, B.; Bellancourt, A.-R.; Iwaniuk, D.; Marchese, S. V.; Südmeyer, T.; Keller, U. (Optics express, 2008)
Semiconductor saturable absorber mirrors (SESAMs) have become a key element of many ultrafast laser sources, enabling passively modelocked lasers with >100 GHz repetition rate or with >10 microJ pulse energy. Precise knowledge of the nonlinear optical reflectivity is required to optimize the SESAMs for self-starting passive modelocking at record high repetition rates or pulse energies. In this article, we discuss a new method for wide dynamic range nonlinear reflectivity measurements. We achieve a higher accuracy (<0.05%) with a simpler and more cost-efficient measurement scheme compared with previous measurement systems. The method can easily be implemented for arbitrary wavelength regions and fluence ranges.